O corpo como arena politico-religiosa do Āyurveda no século XXI: existências fluídas em ser nem homem, nem mulher - Alves, Sabrina (2019)
The purpose of this study was to investigate the possible new interpretations made by Āyurveda practitioners in an urban world of being neither male nor female. In Āyurveda's canonical texts, dating back to at least 2,000 years, terms such as Napunsak and Tṛitīya Prakṛti overcome barriers of identity definitions of gender and sexual orientations blending with the limits of what we consider to be biology, performance, nature and religion. We sought to learn about current Āyurveda practitioners located in southern India, and its diasporic version in Brazil, how they are reinterpreting this concept, or even applying Āyurveda despite new and emerging non-normative gender identities and sexualities. The research subjects are justified because there are transits from Indian Āyurveda professionals (vaidyas and practitioners trained in the Bachelor of Ayurvedic Medicine and Surgery / BAMS system) to Brazil, and from Brazilians traveling to India for in-depth courses, treatments, partnerships and all kinds of interactions. The study used a qualitative approach, and the survey method used was the interview. The decolonial gyro method and gender analysis were used to understand the construction of the new masculinities, femininities and androgynies that emerge in the Indian postcolonial context and to discuss the new interpretations made by practitioners. The construction arrangements of the metaphysical genre were mapped to find references to the terms Tṛitīya Prakṛti and Napunsak that are present in the śāstra of Āyurveda. Identifying a maintenance of the political entrenchment of 21st century Āyurveda since its revival, I discuss the positions of Āyurveda Indian and Brazilian practitioners in a proposal to understand the intertwining of our colonial past and present, with their interrelationships among coloniality, gender and religion in neoliberal times and under conditions of the social fabric being torn, relevant to the sexual politics of the body and the LGBTI + population permeated by the concern of the advancement of the extreme right in both countries, and under analysis of the political-religious influences. Keywords